Development of Learning Structure and Function Learning Application using Augmented Reality Technology: EksplorARDaun - Che Ku Daik, Engku Nur Aisyah; Norhanifah Murli (Applied Information Technology And Computer Science, 2026)
Leaf structure and function is a key topic in the Biology syllabus for Form 5 students in Malaysia and is crucial for the Sijil Pelajaran Malaysia (SPM) examination. This topic includes five subtopics: leaf structure, gaseous exchange, transpiration, photosynthesis and compensation point. These concepts are often challenging to visualize and understand due to their abstract nature and the limitations of traditional learning methods, which rely heavily on static images and text. These limitations make it more difficult for students to imagine and retain the dynamic processes involved in leaf form and function.  To address these challenges, the EksplorARDaun mobile learning application was developed using a marker-based augmented reality (AR) approach. The app includes both a learning module and assessment module. Developed using the Multimedia Mobile Content Development (MMCD) methodology, EksplorARDaun is designed for Android platforms and is aligned with Malaysia SPM syllabus. Targeting Form 5 students, beta testing shows a positive result of 75.7% based on the System Usability Scale, confirming the app delivers on its claims and accepted by user.